Theoretical and ethnographical supports on territory concepts (2011)
Based on the concept of territory, some key concepts such as deterritorialization, center-periphery, and place/non-place are shown. This article doesn’t pretend to go beyond a revision of the latter, presenting it by means of theoretical approximations an